If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36XY + -6(X + Y) + -186 = 0 36XY + (X * -6 + Y * -6) + -186 = 0 36XY + (-6X + -6Y) + -186 = 0 Reorder the terms: -186 + -6X + 36XY + -6Y = 0 Solving -186 + -6X + 36XY + -6Y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '186' to each side of the equation. -186 + -6X + 36XY + 186 + -6Y = 0 + 186 Reorder the terms: -186 + 186 + -6X + 36XY + -6Y = 0 + 186 Combine like terms: -186 + 186 = 0 0 + -6X + 36XY + -6Y = 0 + 186 -6X + 36XY + -6Y = 0 + 186 Combine like terms: 0 + 186 = 186 -6X + 36XY + -6Y = 186 Add '6Y' to each side of the equation. -6X + 36XY + -6Y + 6Y = 186 + 6Y Combine like terms: -6Y + 6Y = 0 -6X + 36XY + 0 = 186 + 6Y -6X + 36XY = 186 + 6Y Reorder the terms: -186 + -6X + 36XY + -6Y = 186 + 6Y + -186 + -6Y Reorder the terms: -186 + -6X + 36XY + -6Y = 186 + -186 + 6Y + -6Y Combine like terms: 186 + -186 = 0 -186 + -6X + 36XY + -6Y = 0 + 6Y + -6Y -186 + -6X + 36XY + -6Y = 6Y + -6Y Combine like terms: 6Y + -6Y = 0 -186 + -6X + 36XY + -6Y = 0 Factor out the Greatest Common Factor (GCF), '6'. 6(-31 + -1X + 6XY + -1Y) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(-31 + -1X + 6XY + -1Y)' equal to zero and attempt to solve: Simplifying -31 + -1X + 6XY + -1Y = 0 Solving -31 + -1X + 6XY + -1Y = 0 Move all terms containing X to the left, all other terms to the right. Add '31' to each side of the equation. -31 + -1X + 6XY + 31 + -1Y = 0 + 31 Reorder the terms: -31 + 31 + -1X + 6XY + -1Y = 0 + 31 Combine like terms: -31 + 31 = 0 0 + -1X + 6XY + -1Y = 0 + 31 -1X + 6XY + -1Y = 0 + 31 Combine like terms: 0 + 31 = 31 -1X + 6XY + -1Y = 31 Add 'Y' to each side of the equation. -1X + 6XY + -1Y + Y = 31 + Y Combine like terms: -1Y + Y = 0 -1X + 6XY + 0 = 31 + Y -1X + 6XY = 31 + Y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3a+5=50 | | 26-n=14+n | | 5x^2-20x-160=0factorise | | x=23-13 | | 99x=88(x+0.5) | | -X^2+13X+15=0 | | 4x^2=0.16x | | log(x)=3.86 | | 3z+6=42 | | -8(x+8)-(-9x-4)=-5 | | 0.01x^2=4 | | 2p+3p+2p+p=-4 | | g(-4n)=n^3-5n^2 | | 36XY-6(X+Y)+(1-C)=0 | | x^2-x+122=0 | | x^2+3x-77=0 | | (16-7)y=1/9 | | -2+7=20 | | (16-7)=1/9 | | 3x+65=52+11 | | 75+20(a-2)= | | 64-32=0 | | (x)(x+9)(x-1)=72 | | 4(4s+6)=232 | | 2(2l+5)=30 | | 3+7x=-15+x | | 7x-49x^2/49x | | 5(a-1)=70 | | 3n+1n=7 | | x-26=3(2x-2) | | 6xy=7x+z | | 3x-75=15 |